Problems and prospects of adoption of E-Commerce in the electronic manufacturing companies in Malaysia - Syed Shah Alam (2004)
The adoption of E-commerce(EC) technologies is revolutionising the way of doing business. Researchers and practitioners have recognised the importance of e-commerce technology and its applications for the success of the organisations. There is an evidence that electronic manufacturing companies in Philippines have benefited through adopting such technologies. However, despite numerous studies about EC there is a dearth of research associated with EC adoption and the factors affecting such adoption. This research attempts to examine the adoption of EC technology by the electronic manufacturing companies in Malaysia using the framework developed by the electronic manufacturing companies in Malaysia using the framework developed on innovation diffusiom theory. Considering the necessity of EC adoption in the electronic manufacturing companies in Malaysia, this study has been designed to investigate the major barriers and benefits perceived by the companies under study and the factors influencing electronic manufacturing companies in Malaysia to adopt EC.